Mechanisms of endonuclease-mediated mRNA decay - Schoenberg, Daniel R. (2011)
Endonuclease cleavage was one of the first identified mechanisms of mRNA decay but until recently it was thought to play a minor role to the better-known processes of deadenylation, decapping and exonuclease-catalyzed decay. Most of the early examples of endonuclease decay came from studies of a particular mRNA whose turnover changed in response to hormone, cytokine, developmental or nutritional stimuli. Only a few of these examples of endonuclease-mediated mRNA decay progressed to the point where the enzyme responsible for the initiating event was identified and studied in any detail. The discovery of microRNAs and RISC-catalyzed endonuclease cleavage followed by the identification of PIN (pilT N-terminal) domains that impart endonuclease activity to a number of the proteins involved in mRNA decay has led to a resurgence of interest in endonuclease-mediated mRNA decay. PIN domains show no substrate selectivity, and their involvement in a number of decay pathways highlights a recurring theme that the context in which an endonuclease functions is a primary factor in determining whether any given mRNA will be targeted for decay by this or the default exonuclease-mediated decay processes.